PG116 'A pilot study' – multi-departmental in situ simulation with human factors feedback delivered by pilots. (10th November 2020) - Lloyd, Robert; Mooncey, Mumtaz; Parker, Lucy; Robinson, Kerry; Baldeweg, Friederikecharlotte; Jolly, Alex
Abstract : Introduction: Approximately 70% of adverse events in healthcare are thought to be attributable to a failure of non-technical performance, including communication, teamwork and leadership. 1 The integration of regular in situ simulation promotes positive team-working relationships. The aviation industry is widely considered to be the gold standard for safety culture. 'On average, just one commercial flight goes down for every 8.3million take-offs worldwide. In the US alone, there are approximately 400, 0000 avoidable medical errors every year, which is the equivalent of two jumbo jet crashes every day'. 2 Enhanced inter-specialty relationships and improved human factors training are both imperative for promoting patient safety. Methods/Project Description: Twenty in situ simulations were facilitated across the hospital. Sims often involved multiple specialties, fostering a collaborative training spirit. Emergency Medicine, Paediatrics, Acute Medicine and Anaesthetics scenarios were facilitated by departmental simulation leads, with logistics support from the Resuscitation Officers. The technical debrief was led by the clinical facilitator, and the human factors debrief was facilitated by airline pilots in attendance. A write-up with key learning points was then distributed to the departments involved within one week. Summary of Results/Outcomes: The write-ups comprised of technical feedback from the medical team and human factors feedback from the pilots. Human factors feedback centred around four key areas: Communication Situational Awareness Workload Management Decision-making A questionnaire survey was used to assess the effects of human factors feedback on both confidence and competence. 94% of participants reported that their understanding of human factors principles improved following simulation. Qualitative evaluation of results was undertaken; comments included: 'Authentic learning experience which highlighted areas of weakness and also given me confidence to 'step up' in a supervised setting'. The feedback was circulated amongst the wider team and shared on the PonderMed blog. 3 Discussion, Conclusions, Recommendations: Parallels were drawn between healthcare and the aviation industry, to highlight key learning points. There were four key concepts repeatedly emphasised (see table 1 below): Table 1. References: Carayon P, Wood KE. Patient safety – the role of human factors and systems engineering. Stud Health Technol Inform 2010;153 :23–46. 'Black Box thinking, 2015. Syed M. PonderMed.co